Intentional spatial coding of responses under multiple action effect situations - Heurley, Loïc P.; Ferrier, Laurent P.; Coutté, Alexandre; Thébault, Guillaume (Frontiers in psychology, 2023)
A major question in cognitive sciences concerns the nature of neurocognitive processes underlying the representation of the body in action [...]. As recently advocated by Pfister (2019), one question becomes of primary importance in this general account: How can people cognitively deal with situations in which a specific action induces various spatially non-congruent action effects at the same time?